Monoclonal Gammopathy of Undetermined Significance Disguised as Chronic Neutrophilic Leukemia - Monique A Hartley-Brown; Lubomir Sokol; Gisela L Caceres; Mohammed A Hussein; Alan List; Javier Pinilla-Ibarz (Mediterranean Journal of Hematology and Infectious Diseases)
A 60-year-old woman with a medical history of diabetes mellitus, osteoporosis, peripheral vascular disease, and hypertension who was otherwise asymptomatic but continued showing elevated neutrophil levels sought a second opinion at our facility. Serum protein immunoelectrophoresis with immunofixation revealed an immunoglobulin A (IgA)-κ monoclonal gammopathy concentration of 1305 mg/dL (normal 80-350 mg/dL) but relatively normal concentrations of IgG of 840 mg/dL (620-1400 mg/dL) and IgM of 36 mg/dL (45-250 mg/dL). Clonal analysis revealed a polyclonal expression pattern in all cell types analyzed. We concluded that our patient’s neutrophilia may have been due to the underlying monoclonal gammopathy. This is the first case in the literature of a patient with monoclonal gammopathy of undetermined significance presenting with neutrophilia, suggestive of chronic neutrophilic leukemia (CNL).  Patients with CNL have a poor prognosis; therefore, it is important to distinguish diagnostically between CNL and the less severe prognosis of monoclonal gammopathy of undetermined significance.